2015
DOI: 10.1021/acs.jafc.5b01975
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Egg Farming Systems from The Netherlands and New Zealand Using Stable Isotopes

Abstract: Stable isotopes were used to develop authentication criteria of eggs laid under cage, barn, free range, and organic farming regimens from The Netherlands and New Zealand. A training set of commercial poultry feeds and egg albumen from 49 poultry farms across The Netherlands was used to determine the isotopic variability of organic and conventional feeds and to assess trophic effects of these corresponding feeds and barn, free range, and organic farming regimens on corresponding egg albumen. A further 52 brands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Similarly fast isotopic changes in rapidly turning over body pools have been documented in mammals and birds (Ayliffe et al ; Podlesak et al ; Sponheimer et al ). Both the egg albumen values and the offsets between egg albumen and diet in both carbon and nitrogen isotopic values show some degree of variability (Table ), but are similar to those found in large‐scale studies of eggs and egg‐laying hens in the Netherlands, New Zealand and Brazil (Madeira et al ; Rogers et al ).…”
Section: Discussionsupporting
confidence: 74%
“…Similarly fast isotopic changes in rapidly turning over body pools have been documented in mammals and birds (Ayliffe et al ; Podlesak et al ; Sponheimer et al ). Both the egg albumen values and the offsets between egg albumen and diet in both carbon and nitrogen isotopic values show some degree of variability (Table ), but are similar to those found in large‐scale studies of eggs and egg‐laying hens in the Netherlands, New Zealand and Brazil (Madeira et al ; Rogers et al ).…”
Section: Discussionsupporting
confidence: 74%
“…There have been some approaches in the past to differentiate between eggs from different housing systems. Some studies analysed the stable isotope ratio of eggs from both different rearing systems and countries, for example, Rogers et al found significant differences in δ 15 N and δ 13 C values. Inácio and Chalk described in general the principles and limitations of this analytical technique when used to differentiate between conventionally and organically produced animal foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Eggs from various systems (1-, 2-, and 3-coded eggs) may be discriminated through fluorescent patterns on egg surfaces or stable nitrogen isotope compositions. Stable isotopes methods were used to develop authentication criteria of eggs laid under cage, barn, free range, and organic farming regimens [305]. Recently, discrimination of selected chicken eggs in China's retail market based on multielement and lipidomic analyses was reported [306].…”
Section: Honey and Other Products Of Animal Originmentioning
confidence: 99%